Development of electric resistance sintering process for the fabrication of hard metals: Processing, microstructure and mechanical properties. (August 2017) - Lagos, M.A.; Agote, I.; Schubert, T.; Weissgaerber, T.; Gallardo, J.M.; Montes, J.M.; Prakash, L.; Andreouli, C.; Oikonomou, V.; Lopez, D.; Calero, J.A.
Abstract: This work presents the development of the Electrical Resistance Sintering (ERS) process for the fabrication of hard metals. The compositions of the materials produced were WC with 6 and 10 wt% of Co. In addition to the specific characteristics of the technology, the characterization of the produced parts is presented and compared to materials obtained by conventional processes. The parts produced by ERS present densities comparable to the ones obtained by conventional methods. The microstructural comparison shows a considerable grain size reduction in the ERS materials which consequently brings a hardness increase. ERS materials show similar fracture toughness to conventional ones. The very fast sintering allows performing the process without any protective atmosphere, therefore making this process very attractive for the production of materials that need to be sintered under non-oxidising environments. The total duration of the cycle, including heating, holding time and cooling is few seconds. Finally, some considerations about the scale up and possible industrialization of the technology are explained. Highlights: Development of a new process for the fabrication of hard metals Specific characteristics of the technology and about the materials produced Microstructural characterization of the obtained products compared to conventional hard metals Mechanical and magnetic characterization of the obtained products compared to conventional hard metals Practical considerations about the technology regarding processing time and energy consumption